TECHNO-ECONOMIC ANALYSIS OF PRODUCTION AND MARKETING OF MARINE BY-PRODUCTS IN INDIA - Sathiadhas, R.; Aswathy, N. (Journal of Indian Fisheries Association, 2015)
Marine by-products coming under the ancillary products group found many applications in pharmaceutical and industrial sectors. Although many of these products are fetching very high price at the export market, adequate statistics regarding their current production, marketing and utilisation is lacking. The present analysis deals with the production potential, level of exploitation, uses, export growth rate and potential for the future of some of these marine by-products. The analysis revealed that an estimated quantity of 205 tonnes of shells, 10 tonnes of gastropod operculum, 4,932 tonnes of shark liver oil and 4,384 tonnes of shark cartilage could be produced annually in India with the current landings. The production potential of chitin is estimated as 3,560 tonnes from shrimp shell wastes and 1,354 tonnes from crab shell wastes. The high unit value of different products clearly indicates the scope for their development by evolving appropriate utilisation and marketing strategies. Keywords: by-products, production potential, marketing, growth rate